2011
DOI: 10.1002/imhj.20291
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of mother–infant psychoanalytic treatment: I. Outcomes on self‐report questionnaires and external ratings

Abstract: Mother-infant relationship disturbances occur in three domains: maternal distress, infant functional problems, and relationship difficulties. They constitute common clinical problems. In Sweden, they are usually handled by nurses as part of public Child Health Centre care. Severe cases are referred to child psychiatry services. This randomized controlled trial compared two groups of mother-infant dyads in a Stockholm sample. One received only Child Health Centre care (the "CHCC" group) while the other received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 61 publications
1
39
2
Order By: Relevance
“…However, their external rating was not blinded with respect to admission or discharge assessment, which may affect the reported intraclass correlation. Moreover, the sample in Salomonsson et al [20] was not comparable to ours, as their PIR-GAS mean scores considerably differed to mean score reported in our sample. Therefore, the results cannot be directly compared with each other.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…However, their external rating was not blinded with respect to admission or discharge assessment, which may affect the reported intraclass correlation. Moreover, the sample in Salomonsson et al [20] was not comparable to ours, as their PIR-GAS mean scores considerably differed to mean score reported in our sample. Therefore, the results cannot be directly compared with each other.…”
Section: Discussioncontrasting
confidence: 86%
“…We do not invalidate these findings with our study, but we questioned the equivalence of a 10-minute rating to a ‘full-information’ condition and did not find evidence that both measures can be used interchangeably. This issue was more closely addressed by the study of Salomonsson et al [20], who reported a high intraclass interrater reliability. However, their external rating was not blinded with respect to admission or discharge assessment, which may affect the reported intraclass correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3rd edition of the EA sensitivity scale shows meaningful relations with child attachment security in risk samples in Western countries (Oppenheim, Koren-Karie, Dolev, & Yirmiya, 2012;Van IJzendoorn et al, 2007) and in a non-Western country (John, Morris, & Halliburton, 2012, in India). The sensitivity scale also relates to parental attachment state of mind (Aviezer, Sagi, Joels, & Ziv, 1999;Coppola, Cassibba, & Costantini, 2007;Edelstein et al, 2004), and has been shown the ability to detect changes in maternal sensitivity following intervention (e.g., Salomonsson & Sandell, 2011).…”
Section: Emotional Availability Scales (Ea Scales)mentioning
confidence: 99%
“…To facilitate the development of more adaptive parenting by the mother, Fraiberg believes that it is important to address the mother's unresolved attachment conflicts as well as more secure and less disorganised attachment between the mother and her infant. A recent randomised-controlled trial of infantmother psychoanalytically informed treatment has shown that this treatment is effective in lowering maternal depression symptoms and in improving the relationship between the mother and infant [27].…”
Section: Parent-infant Psychotherapymentioning
confidence: 99%